(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Currently, inflammatory processes activate various systems in the body. This article reveals the etiology and pathogenesis of odontogenic inflammatory diseases of the maxillofacial region. Special attention is paid to the aggressive course of the inflammatory process with the defeat of deep cellular spaces, accompanied by pronounced endogenous intoxication. The author analyzes the importance of the use of antibiotics from the group of penicillins in the treatment of inflammatory processes of the maxillofacial region.